IMPROVING EFFICIENCY: EXERCISES AND ACTIVITIES AIMED AT DEVELOPING STUDENTS’ ENGLISH COMMUNICATION SKILLS WITH ELECTRONIC PROGRAMS - Khakimov, K.A. (SCIENCE and SOCIETY, 2025)
This article discusses various activities and exercises facilitated by technology that help students improve their English communication skills, with references to recent academic studies.